Attitudes of University Students toward Business Ethics: A Cross-National Investigation of Australia, Singapore and Hong Kong - Phau, Ian; Hwee, Ping kea (Kluwer Academic Publishers, 2006)
With the current globalisation and complexity of today’s business environment, there are increasing concerns on the role of business ethics. Using culture and religion as the determinants, this paper presents a cross-national study of attitudes toward business ethics among three countries: Australia, Singapore and Hong Kong. The results of this paper have shown the attitudes toward business ethics to be significantly different among the three countries. It was also found that respondents who practised their religion tend to consider themselves more ethically minded than those who do not. Additional findings on gender have also revealed significant differences between the males and females for respondents in Singapore and Australia. Males are generally considered more ethical than females across the three countries studied.